An optimal dietary sodium chloride supplemental level of broiler chicks fed a corn-soybean meal diet from 1 to 21 days of age - Zhang, Weiyun; Wu, Bingxin; Wu, Wei; Cui, Xiaoyan; Li, Ding; Gao, Feiyu; Li, Tingting; Zhu, Ling; Geng, Yanqiang; Zhang, Liyang; Hu, Yun; Luo, Xugang (Frontiers in Veterinary Science, 2022)
Sodium chloride (NaCl) is usually added to diets to meet the Na and Cl requirements of broilers in the Chinese poultry industry, but the optimal dietary NaCl supplemental level was not well established. The present study was conducted to estimate the optimal dietary NaCl supplemental level of broilers fed a corn-soybean meal diet from 1 to 21 d of age. A total of 490 one-d-old Arbor Acres male broilers were fed a NaCl-unsupplemented corn-soybean meal basal diet (control) and the basal diet supplemented with 0.10, 0.20, 0.30, 0.40, 0.50 or 0.60% NaCl for 21 d. Regression analysis was conducted to evaluate the optimal dietary NaCl level using the best fitted broken-line or asymptotic models. As dietary supplemental NaCl levels increased, average daily gain (ADG), average daily feed intake (ADFI), blood partial pressure of CO2, total CO2, base excess and anion gap, blood concentrations of HCO3, Na and Cl, serum Na concentration, jejunal villus height (VH) and tibia ash content increased linearly and quadratically (P < 0.05), while feed/gain ratio, relative weights of heart, liver and kidney, blood K concentration, serum concentrations of K, uric acid and glucose, and osmotic pressure decreased linearly and quadratically (P < 0.05). The estimates of optimal dietary NaCl levels were 0.20-0.22% based on the best fitted broken-line or asymptotic models (P < 0.0001) of ADG, ADFI and feed/gain ratio, and 0.08-0.24% based on the best fitted broken-line or asymptotic models (P < 0.0001) of blood gas indices, serum parameters, jejunal VH, tibia ash content and organ indices. These results suggested that the optimal dietary NaCl supplemental level would be 0.24% for broilers fed the corn-soybean meal diet from 1 to 21 d of age, which is lower than the current dietary NaCl supplemental level (0.30%) in the Chinese broiler production.